PERSEPSI NELAYAN MENURUT STRATIFIKASI SOSIAL TENTANG PENDIDIKAN ANAK DI DESA AENG BATU-BATU KEC. GALESONG UTARA KAB. TAKALAR - Hasriyanti, Hasriyanti (LaGeografia, 2019)
This study aims to 1) know the general picture of social stratification, 2) find out the perceptions of fishermen according to social stratification about children's education. The study population was fishermen totaling 456 families. Sampling was done using purposive sampling method with a sample of 40 families. Data were collected using a Likert scale and analyzed using descriptive statistical analysis. The results showed that the social stratification of fishermen was based on objective criteria, namely the possession of fishing production equipment and the level of income divided into 3 strata namely fishermen who had fishing equipment (boats) and had laborers called fishermen fishermen, fishermen who did not have fishing equipment were called laborers, and fishermen who own boats but are operated on their own are called individual fishermen. Fishermen's perception of children's education has 75 percent having high perceptions, and 25 percent having very high perceptions. Based on the average value obtained that is 113 in the range 91-120, it can be said that fishermen in the village of Aeng Batu-Batu have a relatively high perception of children's education.